When ghosts come home [large type] : a novel - Cash, Wiley (Harper Large Print, an imprint of HarperCollinsPublishers, 2021)
In the middle of the night, Sheriff Winston Barnes learns that a plane has crashed at a coastal airfield, with neither pilot nor cargo in evidence and a local man found shot dead, but as Winston investigates, a devious challenger threatens his reelection as sheriff, his daughter returns home with heartbreak of her own, and long-submerged racial bitterness comes to the fore.